Pink-footed Geese Anser brachyrhynchus on the Moorfoot Hills, Scotland, in spring 1952-1981 - Boyd, Hugh (Wildfowl, 1998)
William Brotherston, watching Pink-footed Geese roosting at Fala Moor Loch and feeding on the north slopes of the Moorfoot Hills, Midlothian, Scotland, recorded changes in numbers in spring, the influences of weather and farming practices, sexual behaviour and emigration. Mean peak number were about 3,500 in early April, with the highest count of 7,037 on 10 April 1981. The mean number of goose-days' in March and April was about 230,00 (from 120,000 in 1970 to 400,000 in 1972). More geese were present after mild winters and in warm Aprils. The numbers of geese increased with the area of improved grass, but seem not to have been affected by the numbers of full-grown sheep present. Sexual activities at the roost began in mid-April. The mean date of large northward departures was 1 May (range 19 April to 10 May). Nearly half the migratory movements were seen when the airflows over Scotland seemed unlikely to assist passage to Iceland, though large departures were most likely to occur with following winds.